Modification of cystatin C activity by bacterial proteinases and neutrophil elastase in periodontitis. Issue 6 (December 1997) - Abrahamson, M; Wikström, M; Potempa, J; Renvert, S; Hall, A
Abstract : AIM: To study the interaction between the human cysteine proteinase inhibitor, cystatin C, and proteinases of periodontitis associated bacteria. METHODS: Gingival crevicular fluid samples were collected from discrete periodontitis sites and their cystatin C content was estimated by enzyme linked immunosorbent assay (ELISA). The interaction between cystatin C and proteolytic enzymes from cultured strains of the gingival bacteria Porphyromonas gingivalis, Prevotella intermedia, and Actinobacillus actinomycetemcomitans was studied by measuring inhibition of enzyme activity against peptidyl substrates, by detection of break down patterns of solid phase coupled and soluble cystatin C, and by N-terminal sequence analysis of cystatin C products resulting from the interactions. RESULTS: Gingival crevicular fluid contained cystatin C at a concentration of approximately 15 nM. Cystatin C did not inhibit the principal thiol stimulated proteinase activity of P gingivalis. Instead, strains of P gingivalis and P intermedia, but not A actinomycetemcomitans, released cystatin C modifying proteinases. Extracts of five P gingivalis and five P intermedia strains all hydrolysed bonds in the N-terminal region of cystatin C at physiological pH values. The modified cystatin C resulting from incubation with one P gingivalis strain was isolated and found to lack the eight most N-terminal residues. The affinity of the modified inhibitor for cathepsin B was 20-fold lower (Ki 5 nM) than that of full length cystatin C. A 50 kDa thiol stimulated proteinase, gingipain R, was isolated from P gingivalis and shown to be responsible for the Arg8-bond hydrolysis in cystatin C. The cathepsin B inhibitory activity of cystatin C incubated with gingival crevicular fluid was rapidly abolished after Val10-bond cleavage by elastase from exudate neutrophils, but cleavage at the gingipain specific Arg8-bond was also demonstrated. CONCLUSIONS: The physiological control of cathepsin B activity is impeded in periodontitis, owing to the release of proteinases from infecting P gingivalis and neutrophils, with a contribution to the tissue destruction seen in periodontitis as a probable consequence.